Strongly inhomogeneous distribution of spectral properties of silicon-vacancy color centers in nanodiamonds. (7th November 2018) - Lindner, Sarah; Bommer, Alexander; Muzha, Andreas; Krueger, Anke; Gines, Laia; Mandal, Soumen; Williams, Oliver; Londero, Elisa; Gali, Adam; Becher, Christoph
Abstract: The silicon-vacancy (SiV) color center in diamond is a solid-state single photon emitter and spin quantum bit suited as a component in quantum devices. Here, we show that SiV centers in nanodiamonds exhibit a strongly inhomogeneous distribution with regard to the center wavelengths and linewidths of the zero-phonon-line (ZPL) emission at room temperature. We find that the SiV centers separate in two clusters: one group exhibits ZPLs with center wavelengths within a narrow range ≈730–742 nm and broad linewidths between 5 and 17 nm, whereas the second group comprises a very broad distribution of center wavelengths between 715 and 835 nm, but narrow linewidths from below 1 up to 4 nm. Supported by ab initio Kohn–Sham density functional theory calculations we show that the ZPL shifts of the first group are consistently explained by strain in the diamond lattice. Further, we suggest, that the second group showing the strongly inhomogeneous distribution of center wavelengths might be comprised of a new class of silicon-related defects. Whereas single photon emission is demonstrated for defect centers of both clusters, we show that emitters from different clusters show different spectroscopic features such as variations of the phonon sideband spectra and different blinking dynamics.